The problem of intellectual extremism and its relationship to international terrorism A study in the dialectic of the relationship - Jiyad, Esraa Ahmed (The International and Political Journal, 2022)
A wave of intellectual extremism is sweeping the world today. It is practical and behavioral extremism in most cases that expresses itself with terrorist actions directed against either the state and its institutions or a group of society. These acts had ethnic or religious motives with direct or indirect links with the economic, political, and social situation, such as the spread of unemployment, social injustice, the absence of democratic freedoms, and the blockage of future prospects, which makes the violence through which the prevailing extremism today expresses itself in the form of terrorism in most cases.